In Vitro Transcription of pe38/Polyhedrin Hybrid Promoters Reveals Sequences Essential for Recognition by the Baculovirus-Induced RNA Polymerase and for the Strength of Very Late Viral Promoters - Mans, Ruud M. W. (American Society for Microbiology, 1998)
In vitro transcription was used to analyze the promoter specificity of the α-amanitin-resistant RNA polymerase that is induced late during infection of Autographa californica multicapsid nuclear polyhedrosis virus. By modifying the preparation of crude nuclear extracts, we have established an assay that permits differentiation between weak late and strong very late viral promoters. The virus-induced RNA polymerase initiates at a TAAG sequence motif in both late and very late promoters. Based on the sensitivity of our in vitro transcription system, we have investigated the sequences responsible for a functional TAAG motif and their putative role with respect to the strength of very late promoters. By constructing hybrid promoters between the early pe38 and the very late polyhedrin promoters, we demonstrated that the replacement of 7 nucleotides upstream of the nonfunctional TAAG sequences in the pe38 promoter with the corresponding sequences of the polyhedrin promoter was sufficient for recognition by the virus-induced RNA polymerase. The strength of the very late polyhedrin promoter was established after replacing the 5′ untranslated sequences of the pe38 promoter by those of the polyhedrin promoter in addition to the 7 nucleotides upstream of the TAAG motif.